Comparative analysis of real-time kinematic and PPP techniques in dynamic environment. (15th October 2020) - Alkan, Reha Metin; Erol, Serdar; İlçi, Veli; Ozulu, İ. Murat
Highlights: Both RTK and RT-PPP provide cm-level positioning accuracy in kinematic survey. Using RTK methods in rough topography is limited due to the loss of correction. RTX RT-PPP service compensates for RTK methods disadvantages. RTX RT-PPP provides real-time high accurate seamless positioning. Abstract: The main objective of this study is to assess the performance of the relative Real-time Kinematic (RTK) Global Navigation Satellite System (GNSS) Methods; i.e., Single-baseline & Network RTK, and Real-time Precise Point Positioning (RT-PPP); i.e., Trimble CenterPoint Real Time eXtended (RTX) Correction Service in a dynamic environment. For this purpose, a kinematic test was done within a vessel in Obruk Lake Dam in Çorum province, Turkey. The test area was situated in a deep valley and surrounded by high hills covered with dense trees. The real-time coordinates of each measurement epoch were simultaneously determined with Single-baseline RTK, Network RTK, and RTX RT-PPP methods by using three GNSS receivers. The real-time coordinates obtained from both RTK and RT-PPP methods were compared against the post-processed relative solution epoch-by-epoch. The results show that, the 3D position accuracies of real-time methods were found as ±6 cm, ±3 cm and ±7 cm for Single-baseline RTK, Network RTK and RT-PPP methods, respectively. This study demonstrates that although the Network RTK methods provided the best solution among the others, the positioning did not conduct most of the time due to the loss of cellular connection. This was also partially valid for the Single-baseline RTK method because the corrections from the base station via radio-link couldn't be received due to the rough terrain conditions. However, it was possible to make positioning with RTX Real-time PPP technique using satellite delivery GNSS products (corrections) continuously and in a robust manner within the cm-level accuracy. Our study showed that the use of the global multi-GNSS RTX correction service outcompetes conventional RTK methods with providing consistent, reliable, and seamless cm-level accurate positioning almost without any interruption especially in challenging marine environments with severe terrain obstructions.